Microhardness of remineralized enamel using fluoride varnishes in demineralized premolars with lactic acid, in vitro study - Paredes Quintana, María Cristina (2021)
In its early stages, dental caries, are known as incipient carious lesion, this one, can be reversible through the use of fluoride varnishes. Objective: To evaluate, microhardness surface´s of remineralized dental enamel by applying fluorinated varnishes on enamel block´s of premolars demineralized with lactic acid. Materials and Methods: 45 blocks of dental enamel was microhardness measured. Three indentations were made to obtain the initial Knoop hardness, then the enamel was artificially demineralized, with lactic acid solution (pH4) to form the white spot; the sample was divided into 3 groups (n = 15 / group): A) application of 2.26% fluoride varnish (Duraphat-Colgate); B) application of 0.1% fluoride varnish (Protective Fluorine- Ivoclar) and C) without fluoride´s application. The cyclic pH regime was used for 14 days applying fluoride varnish every 3 days to remineralize the tooth enamel in the experimental groups. At the end, the remineralizing post-treatment hardness was obtained; total 9 indentations for each sample. The data were analyzed using the Kruskall-Wallis test. Results: Significant difference between the groups (p = <0.0001). was found. Dunn’s method was used for comparisons between groups, establishing that enamel´s microhardness was higher, after the application of fluorine varnish at a concentration of 2.26%. Conclusion: Both of them fluorinated varnishes increased the microhardness enamel´s, however, the application of fluoride varnish at 2.26% concentration´ presented higher microhardness. Enamel remineralization was proportional to fluoride concentration.